Approximate solutions of time and time-space fractional wave equations with variable coefficients. Issue 9 (4th July 2018) - Japundžić, Miloš; Rajter-Ćirić, Danijela
Abstract : We consider the Cauchy problem for fractional evolution equations with time fractional derivative as Caputo fractional derivative of order and space variable coefficients on an unbounded domain. The space derivatives that appear in the equations are of integer or fractional order such as the left and the right Liouville fractional derivative as well as the Riesz fractional derivative. In order to solve this problem we introduce and develop generalized uniformly continuous solution operators and use them to obtain the unique solution on a certain Colombeau space. In our solving procedure, instead of the originate problem we solve a certain approximate problem, but therefore we also prove that the solutions of these two problems are associated. At the end, we illustrate the applications of the developed theory by giving some appropriate examples.